King Leopold's ghost a story of greed, terror, and heroism in Colonial Africa - Hochschild, Adam (Houghton Mifflin Company, 1999)
Chronicles the life of King Leopold II of Belgium and discusses how he plundered the Congo, how his people tried to overthrow him, and other related topics.